A Molinist Response to Schellenberg’s Hiddenness Argument - Erasmus Jacobus; Stratton Timothy A. (Perichoresis: The Theological Journal of Emanuel University, 2023)
John Schellenberg argues that divine hiddenness is evidence against God’s existence. More precisely, according to Schellenberg’s well-known Hiddenness Argument, God’s existence entails that there would never be any nonresistant non-believers; however, there are some non-resistant non-believers; therefore, God does not exist. In this paper, we offer a Molinist response or solution to the Hiddenness Argument. First, we briefly explain Molinism, we then describe Schellenberg’s Hiddenness Argument, and, finally, we argue that Molinism undercuts the view that God would necessarily ensure there will never be any nonresistant non-believers.